Moral dilemmas in virtual reality: a narrative review of findings and methodological challenges - Pucci, Margherita; Gagliardi, Lorenzo (Frontiers in Psychology, 2025)
Moral dilemmas have long been challenging to study, as different methods often produce results that are hard to compare depending on how questions are framed and responses elicited. Over the past two decades, however, Virtual Reality (VR) has revolutionized this field by the means of immersive and ecologically valid simulations that better reflect real-life scenarios. This literature review examines the use of VR technologies to investigate moral dilemmas, focusing on how immersive environments affect moral decision-making. By analyzing 29 empirical and theoretical studies, we explore how VR enhances ecological validity, bridges the gap between moral judgment and action, and allows researchers to simulate ethically challenging scenarios that would be impossible to recreate in real life. The review covers classic dilemmas—such as the trolley and footbridge problems—as well as applied contexts like driving scenarios, autonomous vehicle decision-making, and professional ethics training. Across these settings, VR studies consistently reveal a general trend toward utilitarian choices, modulated by contextual factors (e.g., age of victims, time pressure), individual differences, and emotional salience. Furthermore, the paper highlights VR’s capacity to integrate multimodal data, such as physiological responses and eye-tracking, providing a richer picture of moral cognition. In a dedicated section, we review the main methodological arguments in favor of using VR, along with critiques concerning ecological validity, replicability, and ethical risks linked to virtually real experiences. We conclude by outlining recommendations for future research, emphasizing the importance of expanding VR applications, improving methodological standardization, and developing ethically responsible immersive paradigms.